Micro-Teaching and Teaching Practice: A Predictor of Physics Teacher Trainee’s Performance - Bada, Abiodun Adekunle; Akinbobola, Akinyemi Olufunminiyi (Indonesian Journal of Science and Mathematics Education, 2022)
Microteaching and teaching practice are important and compulsory twin course for any teacher trainee student in Nigeria before becoming a professional teacher. The former pave the way for the later and it is intended to prepare teacher trainee for the real teaching practice exercise. This study investigate whether microteaching successfully predict the performance of physics teacher trainees in teaching practice. This investigation is a quantitative research which adopt the ex post facto research design. It involved a cohort of 638 final year Bachelor of Science Education (Physics) students spanning four academic sessions (2015/2016- 2018/2019). The only research question and hypothesis raised were answered and tested using mean/standard deviation and t-test statistics respectively. The result reveal a moderate positive relationship between the performance of physics teacher trainees in microteaching and teaching practice. This study concludes that micro-teaching viably predicted student’s performance in teaching practice.